KAJIAN KOMPUTASI DISTRIBUSI STATISTIK FLUKS NEUTRON DENGAN METODE MONTE CARLO - , Tuti Purwoningsih, Dr. Pekik Nurwantoro ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The migration of a neutron is governed using several probabilities of distribution, such as probability of scattering distribution, probability of distribution apart transfer, probability of distribution of energy transfer, and probability of neutron flux distribution. In this research, study was done for computational about neutron flux distribution pattern in a reactor system. Neutron flux distribution pattern in the reactor is simulated by Matlab using the Monte Carlo method or stochastic method. Variables in this study are the number of neutrons in a simulated system and the depth of cylindrical reactor system. The simulation results for 100,000 neutron takes about 20 â 120 minutes of execution time which depends on the depths of the system. For all of the depths the peak session of neutron flux distribution pattern is in the third bin. The comparison between the simulation results and the other existing results shows that the simulation analysis follows a statistical distribution Maxwell-Boltzmann.